Peran Guru PAI Dalam Membudayakan Literasi Religius Siswa Sma Negeri 1 Mojotengah Wonosobo - Syafa Aulia Hidayah; Fatkhurrohman Fatkhurrohman; Muhammad Saefullah (PT. ALHAFI BERKAH INDONESIA, 2024)
This thesis aims to: 1) understand the religious literacy culture of students at SMA Negeri 1 Mojotengah Wonosobo; 2) determine the role of PAI (Islamic Religious Education) teachers in fostering religious literacy among students at SMA Negeri 1 Mojotengah Wonosobo; 3) assess the impact of religious literacy on the religiosity of students at SMA Negeri 1 Mojotengah Wonosobo. This thesis uses a qualitative research approach, specifically field research. Data collection techniques include observation, interviews, and documentation. Data sources are obtained from primary and secondary sources (religious literacy books, Quran interpretations, theses, journals, and internet sites). The data analysis technique used is an interactive model analysis with three activities: data reduction, data presentation, and conclusion drawing or verification. The research results show that religious literacy culture integrates religious values into life by understanding religious texts to enhance morality, ethics, and spirituality. This includes character building through the teaching of moral and ethical values and the development of critical thinking skills by PAI teachers. PAI teachers act as educators and role models, providing an understanding of Islamic teachings and helping students apply religious values in daily life. They also create a school environment that supports religious literacy culture through religious activities and Islamic extracurricular programs. The positive impacts of religious literacy culture include improved understanding of Islamic teachings, strengthened faith, good behavior, positive traits such as honesty and responsibility, as well as inner peace and emotional well-being. Additionally, this culture teaches the importance of respecting and helping people of different religions and fosters independence in worship and critical thinking.